Construct validity and reliability of the perceived stress scale for nursing students in South Africa - Engelbrecht, Michelle C. (AOSIS, 2022)
Background: Increased levels of stress in nursing students are negatively related to caring behaviours and also result in poorer job proficiency and nurses who are more inclined to leave the profession. The Perceived Stress Scale (PSS), developed by Sheu and colleagues, is one of the most cited instruments for measuring stress and sources of stress amongst nursing students in international studies. However, it has not been widely validated for this purpose. Objectives: This research aimed to test the construct validity and reliability of the PSS for South African nursing students. Method: A cross-sectional survey was conducted at a Central South African University, and 471 of the 685 registered nursing students (68.8% response rate) participated in the study. Questionnaires were distributed and collected during classes. Confirmatory factor analysis was performed to test the hypothesised six-factor latent structure and determine the construct validity of the PSS. The internal consistency of the PSS was measured using Cronbach’s alpha. Results: The model fit was a good fit and supported the six-factor latent structure as stress from (1) taking care of patients, (2) teachers and nursing staff, (3) assignments and workload, (4) peers and daily life, (5) lack of professional knowledge and skills and (6) clinical environment. Overall the PSS had a Cronbach’s alpha of 0.93. Conclusion: The results confirm the construct validity and the internal consistency of the PSS for South African nursing students.
Keywords: Perceived stress scale; Nursing students; Construct validity; Reliability; South Africa